The impact of social media marketing on the attitude and mental health of users: An empirical investigation - Hassan, Haslinda; Mohamad, Rosli; Hsbollah, Hafizah Mohamad (CENTRAL ASIA AND THE CAUCASUS, 2024)
Extant studies have shown that marketers can influence user attitude towards products or services offered by using social media platforms. Evidence also suggests that social media use is associated with a myriad mental health issues, including depression, anxiety, and stress. While the potential of social media platforms for marketing is evident, empirical studies have not fully investigated its impact on user attitude and mental health. The study, therefore, examines the impact of social media marketing (SMM) on user attitude and mental health. A quantitative method was adopted in this study, whereby a questionnaire was distributed to social media users for data collection. Partial Least Squares-Structural Equation Modelling (PLS-SEM) (version 3) was used to analyse the data collected from 203 social media users. Research findings provide support for most hypotheses regarding the significant influence of the variables proposed in the model. The use of SMM affects both cognitive (awareness and knowledge) and affective (liking and preference) attitude, which in turn, affects purchase behaviour. Also, mental health is affected by SMM, but not by purchase behaviour. The findings provide useful insights for the industry and government agencies to better understand the impact of SMM on user attitude and mental health, thereby assisting them to understand consumer behaviour, develop product branding strategies, and establish guidelines that could protect the state of the mental health of users.